Influence of high fructose intake on systemic and cognitive health across developmental stages: A review - Zinhle Mvelase; Mluleki Luvuno; Musa V. Mabandla (Endocrine and Metabolic Science, 2025)
Overconsumption of fructose is a significant medical concern due to its potential adverse effects. In this review article, we critically examine the repercussions of high fructose exposure to increase awareness about the adverse impact of fructose on memory and learning performance, metabolic and systematic parameters with a particular focus on how these manifestations differ among adolescents, children and adults. Chronic intake of high-fructose diets has been consistently associated with impairments in learning and memory functions. These deficits in memory function have been linked to disruptions in insulin signalling pathways in the brain. Scientific evidence further highlights that high fructose intake is attributed to the development of kidney diseases, type 2 diabetes, cardiovascular complications, and an increased risk of Alzheimer's disease. Despite extensive research on fructose's metabolic effects, there are still gaps in understanding its impact on cognitive function and systemic health across different developmental stages.